The Impact of Hybridization on the Volatile and Sensorial Profile of Ocimum basilicum L. (12th January 2014) - Costa, Andréa Santos da; Arrigoni-Blank, Maria de Fátima; Silva, Maria Aparecida Azevedo Pereira da; Alves, Mércia Freitas; Santos, Darlisson de Alexandria; Alves, Péricles Barreto; Blank, Arie Fitzgerald
Abstract : The aim of the present study was to investigate the volatile and sensorial profile of basil ( Ocimum basilicum L.) by quantitative descriptive analysis (QDA) of the essential oil of three hybrids ("Cinnamon" × "Maria Bonita, " "Sweet Dani" × "Cinnamon, " and "Sweet Dani" × "Maria Bonita"). Twelve descriptive terms were developed by a selected panel that also generated the definition of each term and the reference samples. The data were subjected to ANOVA, Tukey's test, and principal component analysis. The hybrid "Cinnamon" × "Maria Bonita" exhibited a stronger global aroma that was less citric than the other samples. Hybridization favored the generation of novel compounds in the essential oil of the hybrid "Sweet Dani" × "Maria Bonita, " such as canfora and (E)-caryophyllene; (E)-caryophyllene also was a novel compound in the hybrid "Sweet Dani" × "Cinnamon"; this compound was not present in the essential oils of the parents.